2005
DOI: 10.1002/marc.200400500
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization and Activation of a Single‐Site Chromium Catalyst for Ethylene Polymerization using MgCl2/AlRn(OEt)3 − n Supports

Abstract: Summary: The effective immobilization and activation of a single‐site chromium catalyst for ethylene polymerization has been achieved using MgCl2/AlRn(OEt)3 − n supports, without the use of methylaluminoxane (MAO) or a borate activator. High catalyst activity and a spherical polyethylene‐particle morphology is obtained. Furthermore, the single‐site characteristics of the catalyst are retained, the narrow molecular weight distribution of the polymers obtained are apparent from gel permeation chromatography (GPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Going beyond the industrially limited scope of vanadium catalysts supported on a glass plate used in this first proof of concept, Rastogi et al. have employed advanced single site catalyst systems to prepare UHMWPE and UHMWPE reactor blends in the unentangled state to achieve high modulus and strength by drawing . Aida et al.…”
Section: All‐hydrocarbon Composites Via Polymerization Catalysismentioning
confidence: 99%
“…Going beyond the industrially limited scope of vanadium catalysts supported on a glass plate used in this first proof of concept, Rastogi et al. have employed advanced single site catalyst systems to prepare UHMWPE and UHMWPE reactor blends in the unentangled state to achieve high modulus and strength by drawing . Aida et al.…”
Section: All‐hydrocarbon Composites Via Polymerization Catalysismentioning
confidence: 99%
“…The support used in this work, obtained via the reaction of MgCl 2 · 1.1EtOH with AlEt 3 , contained 2.7 wt.‐% Al and 5.75 wt.‐% OEt, corresponding to an overall composition MgCl 2 · 0.11AlEt 1.72 (OEt) 1.28 . In previous studies, comparable supports have been used for the immobilization and activation of the chromium catalyst ( η 1 : η 5 ‐Me 2 NCH 2 CH 2 C 5 Me 4 )CrCl 2 , giving high‐molecular‐weight polyethylene having a narrow (Schulz‐Flory) molecular weight distribution 20. The chromium catalyst used in this study was [1‐(8‐quinolyl)indenyl]CrCl 2 ( 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Various studies have shown that supports of type MgCl 2 /AlR n (OR') 3− n , prepared by the reaction of AlR 3 with an MgCl 2 /alcohol adduct, are effective for the immobilization and activation of a wide range of early‐ and late‐transition metal catalysts for ethylene polymerization 17–19. Our previous studies have included the immobilization of a single‐centre chromium catalyst20 and various bis(imino)pyridyl iron catalysts21 on supports prepared by the reaction of AlEt 3 with an adduct MgCl 2 · 1.1EtOH. Such supports have spherical particle morphology and contain a significant proportion of large (>100 nm radius) pores, facilitating monomer diffusion through the growing particle 22.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, various cationic transition metal alkyls with weakly coordinating counter ions were supported on mesoporous inorganic supports without using MAO . Going further beyond using MAO as an activator, Chadwick used MgCl 2 /AlR n (OEt) 3− n , which was produced by the reaction of AlR 3 with adducts of MgCl 2 and ethanol, to activate single‐site catalysts . Moreover, Cramail et al activated rac ‐Et(Ind) 2 ZrCl 2 with adducts of benzoic acid and TMA .…”
Section: Figurementioning
confidence: 99%